Prevalence of human leptospirosis in the Americas: a systematic review and meta-analysis - Ericka Souza Browne; Marcos Pereira; Ana Barreto; Caio Graco Zeppelini; Daiana de Oliveira; Federico Costa (Pan American Health Organization, 2023)
Objective. To describe the prevalence of leptospirosis in the Americas. Methods. A systematic review and meta-analysis, in the period 1930 to 2017, performed on a search of six platforms: PubMed, Web of Science, Scopus, Lilacs, Embase, and Cochrane. Results. The search found 77 publications of which 53 (68%) were from the period 2000-2017. Of the 77, 62 studies were included in the analysis, from North America (11, 17%), Central America (9, 14%), and South America (42, 67%), and 22 studies were from urban areas. Leptospirosis prevalence in the 62 studies analyzed corresponded to 28% (95% CI [23, 32]). Countries with higher prevalence were United States of America (41%), Colombia (29%), and Brazil (21%). The most frequent serovars found were Icterohaemorrhagiae (43 of 77 publications, 55%), Canicola (35, 45%), Pomona (28, 36%), and Grippotyphosa (26, 33%). Conclusions. There is variability of Leptospira species and serovars with heterogenous distribution throughout the Americas, with high prevalence in some countries, highlighting the need for action to control the disease.